PEMIKIRAN PENDIDIKAN TASAWUF PERSPEKTIF BUYA SYAKUR YASIN (STUDI PENDEKATAN BIOGRAFI) - Sukarno Sukarno Sukarno (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractEducation is the most effective tools to change human paradigm as with this humans can acquired the knowledge. Sufism teaches us to have inner peace and sincerity that prioritizes humanity above all. The problems in this research are (1) Who is Buya Syakur Yasin; (2) How is the concept of Sufism education in Buya Syakur Yasin's perspective; (3) How are the teachings of Buya Syakur Yasin's Sufism education. This study has the objectives to: (a) find out Buya Syakur Yasin; (b) Knowing the concept of Sufism education in Buya Syakur Yasin's perspective (c) Knowing the teachings of Buya Syakur Yasin Sufism education. This research method uses a qualitative approach. Data collection in this research is conducted through a series of observations, interviews, and documentation. The conclusion of this study is that Buya Syakur Yasin was born in Indramayu on February 2. According to Buya Syakur Yasin, Sufism is a process of educating our hearts in choosing between good and bad; and Buya Syakur's Sufism Education Teachings including the dhikr istighosah, tahlilan and wiridan ar-razaq, and Kholwat which is held once in a year every 1 dzulkodah to 10 dzulhijah and take a place in the forest for 40 days; by fasting and reciting ar-razaq and wiridan.Keywords :Education, Sufism, Buya Syakur Yasin